Litero-numeracy skills as determinants of secondary school students' achievement in biology (2015)
This study examined the extent to which secondary school students were equipped with basic numeracy and literacy skills required for optimum performance in Biology, investigated the nature and direction of relationship among literacy, numeracy and students' Biology achievement and determined which skills (literacy or numeracy) will significantly predict student's achievement in Biology. The study adopted survey design of correlational research type. The two educational zones were purposively selected out of which a total sample of 200 participants were drawn. Two instruments: Biology Achievement Test (BAT,) r=0.75 and Literacy-Numeracy Self-Efficacy Scale (LNSES) r=0.85were used for data collection. The findings revealed that both numeracy and literacy skills jointly and significantly contribute to student's Biology achievement F(2,196)=l\4.431, p<0.05, Furthermore, numeracy and literacy! can both relatively and significantly predict student's Biology achievement; Literacy Skill fi = (.315), t(200) = 4.525, p=.000, Numeracy Skills fi = (-.285), t(200) = -4.084, p=.000. The outcome of the study revealed that literacy> and numeracy could determine and predict student's achievement in Biology. Hence, it was recommended that in developing subject combination for Biology students, curriculum developers should combine subjects that will aids numerical and literacy ability/skills. of the Biology students because of their negative correlation with Biology achievement.